2014
DOI: 10.5014/ajot.2014.011668
|View full text |Cite
|
Sign up to set email alerts
|

Postdeployment Driving Stress and Related Occupational Limitations Among Veterans of Operation Iraqi Freedom and Operation Enduring Freedom

Abstract: Difficulty in driving after deployment has emerged as an impediment for servicemembers returning from Operation Iraqi Freedom and Operation Enduring Freedom (OIF-OEF). This study explored postdeployment driving stress and related occupational limitations using two self-report instruments: the Driver's Stress Profile and the Driving and Occupational Limitations questionnaire. Data gathered from 103 OIF-OEF returnees confirmed that driving and related occupational issues occur postdeployment. Significant low to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Difficulties with travelrelated hypervigilance, disorientation, and aggression are shown to be further elevated in service members with symptoms of posttraumatic stress (Classen et al, 2017;Kuhn, Drescher, Ruzek, & Rosen, 2010;Lew et al, 2011), placing this population at greater risk for negative social, health, and financial outcomes associated with collisions and repeated citations (e.g., Hickling, Blanchard, Silverman, & Schwarz, 1992;Mayou, Bryant, & Ehlers, 2001; Possis et al, 2014). Despite recognition as a significant veteran health issue (Hwang, Peyton, Kim, Nakama-Sato, & Noble, 2014;Possis et al, 2014;Zinzow, Brooks, & Stem, 2013), few measures have been validated to assess problematic driving in former military. The aim of the current study was to examine the psychometric properties of the Driving Behavior Survey -a measure of anxiety-related driving behavior -in veterans completing a larger study involving the treatment of posttraumatic stress disorder (PTSD; Sloan, Unger, Lee, & Beck, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulties with travelrelated hypervigilance, disorientation, and aggression are shown to be further elevated in service members with symptoms of posttraumatic stress (Classen et al, 2017;Kuhn, Drescher, Ruzek, & Rosen, 2010;Lew et al, 2011), placing this population at greater risk for negative social, health, and financial outcomes associated with collisions and repeated citations (e.g., Hickling, Blanchard, Silverman, & Schwarz, 1992;Mayou, Bryant, & Ehlers, 2001; Possis et al, 2014). Despite recognition as a significant veteran health issue (Hwang, Peyton, Kim, Nakama-Sato, & Noble, 2014;Possis et al, 2014;Zinzow, Brooks, & Stem, 2013), few measures have been validated to assess problematic driving in former military. The aim of the current study was to examine the psychometric properties of the Driving Behavior Survey -a measure of anxiety-related driving behavior -in veterans completing a larger study involving the treatment of posttraumatic stress disorder (PTSD; Sloan, Unger, Lee, & Beck, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of morbidity, accident risk, and global impairment as a result of negative traffic events has triggered interest in identifying factors associated with problematic driving in current and former service members (e.g., Hwang et al, 2014;Lew et al, 2011;Possis et al, 2014;Zinzow et al, 2013). Much of the existing work in this area targets the role of negligent or impulsive behaviors such as speeding, disregarding traffic laws, failing to utilize safety restraints, and driving under the influence of alcohol or substances (e.g., Fear et al, 2008;Hoggatt et al, 2015;Sheppard & Earleywine, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-occurrence of PTSD and TBI can have overlapping physical, cognitive, and psychological symptoms (Bryant, 2011;Miles, Graham, & Teng, 2015;Speicher, Walter, & Chard, 2014;Spencer, Drag, Walker, & Bieliauskas, 2010). These cognitive, psychological, and behavioral impairments can affect reintegration into civilian roles and participation in occupations (Hwang, Peyton, Kim, Nakama-Sato, & Noble, 2014;Radomski & Brininger, 2014;Speicher et al, 2014). These studies stated that concerns can include driving in the community; resuming household, family, work, and leisure roles; self-management of stress and pain; and establishing healthy routines.…”
mentioning
confidence: 99%
“…Appreciably high incidences of functional impairments, irrespective of diagnostic presence, affect this veteran cohort Sammons & Batten, 2008;Tanielian & Jaycox, 2008). Some studies identified stress with everyday civilian tasks (a component of reintegration), such as driving, to be associated with limited participation in society (Hwang, Peyton, Kim, Nakama-Sato, & Noble, 2014;Mattocks et al, 2012). However, Hwang and colleagues did not explore potential confounding diagnoses or symptoms.…”
Section: Stressor Experiences and Reactionsmentioning
confidence: 97%